Factors Affecting Human Resource Development for Industry 5.0 in Thailand - Panapongpaisan, Sirichai; Sukamongkol, Yod (Journal of Mobile Multimedia, 2026)
As Thailand’s manufacturing sector advances toward the human-centric collaborative paradigm of Industry 5.0, identifying the factors that shape organizational preparedness has become a strategic concern. This study investigates how transformational leadership, individual self-efficacy, and collective team effectiveness contribute to Industry 5.0 readiness within the Thai industrial context. A quantitative design was employed, drawing on survey data from 400 manufacturing professionals. The dataset was analyzed using structural equation modeling (SEM) with bootstrapped confidence intervals to assess both direct and mediated effects. The analysis demonstrates that transformational leadership enhances both self-efficacy (β = 0.334, p < 0.001) and team effectiveness (β = 0.285, p < 0.001). Self-efficacy, in turn, strongly improves team outcomes (β = 0.683, p < 0.001). Team effectiveness emerges as the most influential direct predictor of Industry 5.0 readiness (β = 0.757, p < 0.001), while also mediating the influence of leadership and self-efficacy. Collectively, these results confirm that leadership, confidence, and teamwork operate as interdependent drivers of organizational transformation. Theoretically, this research advances understanding of human resource development for Industry 5.0 by clarifying the mechanisms linking leadership, individual capability, and team performance. The findings extend social cognitive theory by validating collective efficacy as a critical mediating mechanism in Industry 5.0 preparedness. Practically, results recommend that human resource managers prioritize high performing team models, while Government agencies should operationalize policy around a human capital preparation index to guide upskilling initiatives.